Variation and Association of Avian β-Defensin 2 Gene with the Concentration of Immunoglobulin Y and the Titer of Newcastle-Disease Antibody in IPB-D1 Chicken - D. Lestari; Masruroh; I. Khaerunnisa; S. Murtini; N. Ulupi; A. Gunawan; C. Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2022)
Defensins play roles in innate immunity by exhibiting antimicrobial activity against microbes such as gram-negative and -positive bacteria, viruses, and fungi. This study aimed to identify variants of the Avian β-Defensin 2 (AvBD2) and determine their associations with the concentration of immunoglobulin Y and the titer of Newcastle disease (ND) antibody in IPB-1 chicken. The chicken population used in this study was 21-week-old IPB-D1 chickens (n=90). Variations in AvBD2 were analyzed by direct DNA sequencing. IgY concentration was measured by indirect ELISA, and the titer of ND antibody was measured by the hemagglutination-inhibition test. The AvBD2 association was analyzed by the general linear model procedure and Duncan’s multiple range test. The results revealed 10 SNPs located in intron 1 (3 SNPs), exon 2 (3 SNPs), and intron 2 (4 SNPs). Six of these SNPs were associated with IgY concentration. The CC genotype of g.5002 C>T was associated with IgY concentration and produced the highest mean IgY concentration. This g.5002 C>T mutation results in alanine-to-valine substitutions. The CC genotype of g.5002 C>T could be considered as a criterion for selecting chickens with high IgY concentrations.